Comparative Evaluation of Two Branched-DNA Human Immunodeficiency Virus Type 1 RNA Quantification Assays with Lower Detection Limits of 50 and 500 Copies per Milliliter - Manegold, Christoph (American Society for Microbiology, 2000)
We have comparatively evaluated Quantiplex version 3.0 and version 2.0 on 133 plasma samples and a repetitive dilution series. Version 3.0 yielded higher human immunodeficiency virus RNA values, and the ratio of version 3.0 results to version 2.0 results decreased from 3.47 below 1,000 copies/ml to 1.97 above 50,000 copies/ml [linear regression, log (version 3.0) = 0.915 + 0.871 × log (version 2.0); r(2) = 0.952].